Quasi-static and fatigue bending behavior of a continuous fiber-reinforced thermoplastic/metal laminate. (1st October 2019) - Zopp, Camilo; Dittes, Axel; Nestler, Daisy; Scharf, Ingolf; Kroll, Lothar; Lampke, Thomas
Abstract: Thermoplastic hybrid laminates are a novel class of material compounds that offer the possibility for large-scale production routes. The laminates consist of an assembly of fiber-reinforced semi-finished layers and metallic sheets in an alternating arrangement. Through the targeted combination of the individual sub-components, a high performing lightweight material with tailor-made properties is achieved. The paper focuses on an advanced thermoplastic hybrid laminate of the CAPAAL type, which is made up of continuous carbon fiber-reinforced polyamide sheets, aluminum top sheets and with continuous glass fiber-reinforced polyamide interlayers in between. The mechanical performance under quasi-static and 3-point bending fatigue, the corresponding damage as well as failure mechanisms are investigated. Under quasi-static bending, a comparatively high stiffness (52 GPa) and strength (645 MPa) in comparison to the commercially established thermosetting hybrid laminates were achieved while even at high strains no interfacial delamination was observed. The bending fatigue tests show that pure elastic loading of the laminate is below the fatigue limit and the laminate withstands one million load cycles without any measurable damages in the individual sub-components. Higher loads are leading to crack propagation inside the aluminum top sheet, whereas only the highest loads applied induced additional damage occurrence inside the thermoplastic matrix. For the first time, investigations on the mechanical performance of a CAPAAL type hybrid laminate under fatigue bending loads are presented. Hereby, in combination with the fast manufacturability of the laminate as a semi-finished product and its subsequent high formability, the suitability for e.g. automotive applications is demonstrated.